A statistical analysis of varying α data - Kraiselburd, Lucila (2014)
We collect different groups of data of the variation of the fine structure constant to compare and verify the consistency between them using the Student test and Confidence Intervals. We separate data sets in smaller intervals based on a proposed criterion. Another statistical analysis is proposed that considers phenomenological models for the variation in α. The results show consistency for a certain amount of reduced intervals, in contrast to those obtained considering the mean values from the entire interval.